ANALISIS DAMPAK DARI KERUGIAN MASKAPAI PT GARUDA INDONESIA PADA SEGI OPERASIONAL PESAWAT UDARA DI BANDAR UDARA INTERNASIONAL NGURAH RAI BALI WILAYAH KERJA KANTOR OTORITAS BANDAR UDARA IV - M Raikal S Gafar; Zenita Kurniasari (Lembaga Pengembangan Kinerja Dosen, 2022)
The covid pandemic has had a major impact on the business of a state-owned airline that has awards in the world of international aviation, namely Garuda Indonesia. This big impact is in the form of a decrease in flight activities so that it affects airline revenues due to regulations issued by the government such as lock down, social distancing and others. From this regulation, Garuda Indonesia's airline business suffered losses. The purpose of this study is 1) to determine the cause of the loss of the airline PT. Garuda Indonesia. 2) To find out the impact of the loss of the airline PT. Garuda Indonesia against aircraft operations at Bali's Ngurah Rai International Airport. This study uses a qualitative method. Data collection instruments were interviews, observations and documentation with supporting documents at Garuda Indonesia and the air transportation unit at the Airport Authority Office IV. To answer the formulation of the research problem, the researchers carried out 3 stages of analysis consisting of data reduction, data presentation, and conclusion drawing. The results of this study show that 1) There are 3 factors that cause losses to Garuda Indonesia airline, namely the covid pandemic, aircraft rental financing and corruption cases in the procurement of ATR and Bombardier aircraft. 2) The impact given to GA's losses in terms of operations, there are 2 factors, namely operating activities which are few compared to the time slot owned by Garuda Indonesia, which is certainly different from the period before the covid pandemic, and a reduction in the operational route of Garuda Indonesia aircraft, namely BDO-DPS which did not propose this route for operation in 2022 with the reason to reduce Garuda Indonesia's cost burden which is certainly different from the period before covid, this route was operated.